The Concomitant Use of Melatonin and Molnupiravir in the Treatment of COVID-19: Mini Review (Bangladesh Journal of Medical Science, 2023)
With the ongoing pandemic declared by the World Health Organization,the number of hospitalizations and deaths caused by COVID-19 is increasing dramatically. As new variants of SARS-CoV-2 emerge, new combination therapies are needed to reduce the risk of COVID- 19spreadduring this time of increased transmission risk. In this case, it is vitalto strengthen the immune system against highly inflammatory conditions such as the cytokine storm caused by COVID-19. This brief review highlights the benefits of taking melatonin and the new antiviral drug molnupiravir together in the treatment of COVID-19. Webelieve that this combination therapy against COVID-19 would be of great benefit and should be considered as an adjuvant therapy in the treatment of this disease.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 32-37